2021
DOI: 10.1371/journal.pntd.0009189
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of praziquantel has been maintained over four decades (from 1977 to 2018): A systematic review and meta-analysis of factors influence its efficacy

Abstract: Background The antihelminthic drug praziquantel has been used as the drug of choice for treating schistosome infection for more than 40 years. Although some epidemiological studies have reported low praziquantel efficacy in cure rate (CR) and/or egg reduction rate (ERR), there is no consistent robust evidence of the development of schistosome resistance to praziquantel (PZQ). There is need to determine factors that lead to variable treatment CR and/or ERR. Therefore, we conducted a systematic review and meta-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 59 publications
1
21
0
1
Order By: Relevance
“…Notwithstanding these reports—and although resistance to praziquantel can be induced in the laboratory—and can emerge in natural populations 30 , there remains no conclusive evidence for its establishment in the field and the topic remains controversial 25 , 33 , 34 . Moreover, a recent meta-analysis found that the efficacy of praziquantel has been maintained since its introduction as the preferred treatment for SCH in the late 1970s 35 .…”
Section: Heterogeneity In Treatment Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Notwithstanding these reports—and although resistance to praziquantel can be induced in the laboratory—and can emerge in natural populations 30 , there remains no conclusive evidence for its establishment in the field and the topic remains controversial 25 , 33 , 34 . Moreover, a recent meta-analysis found that the efficacy of praziquantel has been maintained since its introduction as the preferred treatment for SCH in the late 1970s 35 .…”
Section: Heterogeneity In Treatment Responsesmentioning
confidence: 99%
“…Praziquantel is used exclusively for PC regimens against SCH, typically given at a dose of 40 mg/kg. Some (but not all 47 ) studies have shown 60 mg/kg (typically divided into three 20 mg/kg doses given over the course of a single day) to be more efficacious than the single 40 mg/kg dose 19 , 35 , 48 , 49 . There also exists evidence that repeated doses of praziquantel may improve responses 50 and that co-administration of food increases bioavailability 51 , 52 , which is increasingly recommended as best practice in MDA.…”
Section: Heterogeneity In Treatment Responsesmentioning
confidence: 99%
“…Schistosomiasis, as well as several other parasitic flatworm infections [ 2 ], are treated using the anthelmintic drug praziquantel (PZQ). PZQ has remained an effective treatment for schistosomiasis over four decades of clinical use [ 3 ], underpinning recent mass drug administration (MDA) campaigns aimed at decreasing infections and morbidity in vulnerable populations. Alternatives to PZQ are however needed.…”
Section: Introductionmentioning
confidence: 99%
“…The immunologic character of the glomerular lesion in S. mansoni is one of the postulated mechanisms. 7 , 13 , 15 , 22 , 38–40 …”
Section: Discussionmentioning
confidence: 99%